Contributions to Mineralogy and Petrology - Contributions to Mineralogy and Petrology (Springer Nature, 2026)
Contributions to Mineralogy and Petrology is an international journal that accepts high quality research papers in the fields of igneous and metamorphic petrology, geochemistry and mineralogy. Manuscripts should advance our understanding of the fundamental processes that lead to the formation and evolution of the Earth’s crust, mantle and core. Papers should use petrologic, geochemical and mineralogical evidence recorded in rocks and minerals, or experimental approaches, to explore these processes and their implications for the development of the Earth’s crust, mantle and core through time. Papers concerning ore deposits should specifically focus on experimental research or the mineralogy, petrology and petrologic processes involved in their formation.
FI 1.15
Q1
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geología; Geofísica; Acuerdos transformativos; Transformative agreements; Petrología ígnea; Petrología metamórfica; Geoquímica; Mineralogía